Self-field effects on critical current values in Tl-1223 tapes - Fox, S; Moore, J; Jenkins, R; Grovenor, C; Boffa, V; Bruzzese, R; Jones, H (1996)
We have measured the properties of a large number of Tl-1223 tapes as part of a programme to optimise the fabrication procedures. During this work we have noticed that the highest Ic values are not proportionally dependent on the cross-sectional geometry of the tapes. There seems to be a limiting Ic value of around 10-13 A in our samples (and those of many other groups). We have performed a series of experiments on self-field effects in Tl-1223 tapes and compared the results with calculated field distributions in tape-shaped conductors in different configurations. We conclude that the Ic are self-field limited in these tapes when the currents being carried are around 10 A.